A Study of the Impacts of Air Pollution on the Agricultural Community and Yield Crops (Indian Context) - Pandya, Sharnil; Gadekallu, Thippa Reddy; Maddikunta, Praveen Kumar Reddy; Sharma, Rohit (Sustainability, 2022)
Air pollution has been an vital issue throughout the 21st century, and has also significantly impacted the agricultural community, especially farmers and yield crops. This work aims to review air-pollution research to understand its impacts on the agricultural community and yield crops, specifically in developing countries, such as India. The present work highlights various aspects of agricultural damage caused by the impacts of air pollution. Furthermore, in the undertaken study, a rigorous and detailed discussion of state-wise and city-wise yield-crop losses caused by air pollution in India and its impacts has been performed. To represent air-pollution impacts, the color-coding-based AQI (Air Quality Index) risk-classification metrics have been used to represent AQI variations in India’s agrarian states and cities. Finally, recent impacts of air pollution concerning AQI variations for May 2019 to February 2020, Seasonal AQI variations, impacts of PM2.5, and PM10 in various agrarian states and India cities are presented using various tabular and graphical representations.